Performance of Simplex Signaling in Circular Trellis-Coded Modulation - Alder, Frank A.; Dill, Jeffrey C.; Lindsey, Alan R. (Digital signal processing, 2001)
Alder, F. A., Dill, J. C., and Lindsey, A. R., Performance of Simplex Signaling in Circular Trellis-Coded Modulation, Digital Signal Processing 11 (2001) 159–167 This paper presents measures of performance of simplex signaling in a circular trellis-coded modulation (CTCM) scheme. Background is given on both CTCM and simplex signaling. The CTCM system is shown to give substantial coding gain when compared to conventional BPSK. Performance is also shown to improve as trellis size increases.